The Results of High-dose Rate Intracavitary Brachytherapy for Uterine Cervical Carcinoma in Ramathibodi Hospital - Chuleeporn Jiarpinitnun (2022)
Objectives: To study results of high-dose-rate brachytherapy (HDR-BCT) for the treatment of cervical cancer patients in Ramathibodi Hospital in terms of tumor control, survival and treatment complications and to identify factors that may impact on local control. Materials and Methods: Retrospective analysis was performed on patients with stage IA-IVA cervical cancer treated with a combination of external beam radiotherapy (EBRT) and HDR-BCT in Ramathibodi hospital during March 1999 to June 2001. The Kaplan-Meier method was used for survival analysis. Univariate and Multivariate analysis was performed using log-rank test and Cox proportional hazard regression model to identify factors associated with local control rates. Results: There were 263 patients included in this study (5.3% stage I, 52.8% stage II, 41.8% stage II). The median follow-up time was 66 months (3-113 months). Seventy-one patients (27%) were lost to follow-up. Chemotherapy was delivered in 45 patients. Early stage patients received 40-50.4 Gy whole pelvic EBRT plus 3-4 intracavitary brachytherapy sessions with a fraction size of 3-7 Gy. Patients with advanced stage underwent EBRT to the pelvis to a dose of 40-60 Gy followed by 2-4 sessions of HDR- BCT of 4-7.5 Gy. Median low-dose-rate equivalent dose at point A was 73 Gy and 75 Gy in early and advanced stage, respectively. The 5-year overall survival, disease-free, and local control rates for all patients were 70%, 70%, and 80%, respectively. The 5-year LC rates according to stage were 92% in early stage and 77% in advanced stage. Stage and quality of brachytherapy were independent prognostic factors of local control. Severe (grade 3 and 4) late GI and GU complication rates were 3.1%, and 1.6%, respectively. Conclusion: The combination of EBRT and HDR-BCT, as used in Ramathibodi hospital, can produce favorable outcome and acceptable rates of late complication when compared to other centers in treatment of cervical cancer.